2022
DOI: 10.1021/acs.est.1c07562
|View full text |Cite
|
Sign up to set email alerts
|

Brain Accumulation and Toxicity Profiles of Silica Nanoparticles: The Influence of Size and Exposure Route

Abstract: Nanoparticles (NPs) can make their way to the brain and cause in situ damage, which is a concern for nanomaterial application and airborne particulate matter exposure. Our recent study indicated that respiratory exposure to silica nanoparticles (SiO2 NPs) caused unexpected cardiovascular toxic effects. However, the toxicities of SiO2 NPs in other organs have warranted further investigation. To confirm the accumulation of SiO2 NPs in the brain, we introduced SiO2 NPs with different diameters into mice via intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…33 In addition, model FPMs with simple compositions, such as silica (SiO 2 ) particles, aluminum oxide (Al 2 O 3 ) particles, and microplastics (fluorescent polystyrene) particles, were chosen to represent the real PMs according to the major components of dust samples and model FPMs applied in previous studies. 33 , 40 , 41 The SEM images showed that the five model particles appeared in different morphologies, but all had a size of approximately 2 μm ( Figure S1 ), consistent with the size of real FPMs. In specific, the SiO 2 and FPS particles were spheres with smooth surfaces, and BC particles appeared as sheet-like morphologies.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…33 In addition, model FPMs with simple compositions, such as silica (SiO 2 ) particles, aluminum oxide (Al 2 O 3 ) particles, and microplastics (fluorescent polystyrene) particles, were chosen to represent the real PMs according to the major components of dust samples and model FPMs applied in previous studies. 33 , 40 , 41 The SEM images showed that the five model particles appeared in different morphologies, but all had a size of approximately 2 μm ( Figure S1 ), consistent with the size of real FPMs. In specific, the SiO 2 and FPS particles were spheres with smooth surfaces, and BC particles appeared as sheet-like morphologies.…”
Section: Resultssupporting
confidence: 54%
“…Hereby, different types of FPMs, that is, dust, SiO 2 particles, BC, microplastic particles, and Al 2 O 3 particles were chosen to represent the real FPMs because these compositions were commonly found in atmospheric environments. , The dust sample is a mixture of ambient fine particles containing silica (69–77%), aluminum oxide (8–14%), and other minerals taken from the real environment and is commonly applied to represent real PMs . In addition, model FPMs with simple compositions, such as silica (SiO 2 ) particles, aluminum oxide (Al 2 O 3 ) particles, and microplastics (fluorescent polystyrene) particles, were chosen to represent the real PMs according to the major components of dust samples and model FPMs applied in previous studies. ,, The SEM images showed that the five model particles appeared in different morphologies, but all had a size of approximately 2 μm (Figure S1), consistent with the size of real FPMs. In specific, the SiO 2 and FPS particles were spheres with smooth surfaces, and BC particles appeared as sheet-like morphologies.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In mammals, inhaled NPs were found to elicit severe pulmonary diseases, such as inflammation, , fibrosis, and tumor metastasis . In addition, epidemiological studies have indicated that airborne NPs may penetrate lung tissue, circulate in blood, and affect other organs, such as the heart, liver, kidney, and brain, causing cardiovascular or neurological diseases . Ibanez et al visualized the particle distributions in extrapulmonary organs of mice that received aerosol inhalation of UO 4 NPs and detected elemental uranium in the mouse brain after 4 h .…”
Section: Introductionmentioning
confidence: 99%